97.9k views
4 votes
Use the method of reduction of order to find a second solution to t^2y' + 3ty' – 3y = 0, t> 0 Given yı(t) = t y2(t) = Preview Give your answer in simplest form (ie no coefficients)

User Monsur
by
5.2k points

1 Answer

5 votes

Let
y_2(t)=tv(t). Then


{y_2}'=tv'+v


{y_2}''=tv''+2v'

and substituting these into the ODE gives


t^2(tv''+2v')+3t(tv'+v)-3tv=0


t^3v''+5t^2v'=0


tv''+5v'=0

Let
u(t)=v'(t), so that
u'(t)=v''(t). Then the ODE is linear in
u, with


tu'+5u=0

Multiply both sides by
t^4, so that the left side can be condensed as the derivative of a product:


t^5u'+5t^4u=(t^5u)'=0

Integrating both sides and solving for
u(t) gives


t^5u=C\implies u=Ct^(-5)

Integrate again to solve for
v(t):


v=C_1t^(-6)+C_2

and finally, solve for
y_2(t) by multiplying both sides by
t:


tv=y_2=C_1t^(-5)+C_2t


y_1(t)=t already accounts for the
t term in this solution, so the other independent solution is
y_2(t)=t^(-5).

User Lorenzo Melato
by
5.2k points